2019
DOI: 10.1080/14616734.2019.1589067
|View full text |Cite
|
Sign up to set email alerts
|

Father-child attachment in adoptive gay father families

Abstract: We gratefully acknowledge the children and parents who participated in the study. We would also like to thank Catherine Jones for her help in coding FFIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
2
9
0
1
Order By: Relevance
“…Children also did not differ as a function of family type (lesbian, gay, or heterosexual parents) in their reports of parentchild relationship quality when they were in middle childhood (W2); children generally described high-quality relationships with their adoptive parents. Our finding aligns with the broader literature on child outcomes, parenting, and family relationships among LG parent families indicating healthy and close parent-child relationships with no differences as compared to heterosexual parent families, further underscoring the greater significance of family processes over family structure to individual and family adjustment (Erich et al, 2009b;Golombok et al, 2014Golombok et al, , 2018Carone et al, 2018;McConnachie et al, 2019). Previous studies, however, have generally assessed parent-child relationships from parents' perspectives or via video-recorded observations of parent-child interaction (with the exception of McConnachie et al's interview-based study with children in middle childhood-average age of 11 years).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Children also did not differ as a function of family type (lesbian, gay, or heterosexual parents) in their reports of parentchild relationship quality when they were in middle childhood (W2); children generally described high-quality relationships with their adoptive parents. Our finding aligns with the broader literature on child outcomes, parenting, and family relationships among LG parent families indicating healthy and close parent-child relationships with no differences as compared to heterosexual parent families, further underscoring the greater significance of family processes over family structure to individual and family adjustment (Erich et al, 2009b;Golombok et al, 2014Golombok et al, , 2018Carone et al, 2018;McConnachie et al, 2019). Previous studies, however, have generally assessed parent-child relationships from parents' perspectives or via video-recorded observations of parent-child interaction (with the exception of McConnachie et al's interview-based study with children in middle childhood-average age of 11 years).…”
Section: Discussionsupporting
confidence: 86%
“…There is overwhelming consensus in the scholarly literature that children in LG parent families (including those formed through adoption) are well-adjusted and show high-quality parent-child relationships (Erich et al, 2009a,b;Patterson, 2017;Calzo et al, 2019;McConnachie et al, 2019). Indeed, few differences in outcomes have been uncovered in comparing children in LG parent families versus those in heterosexual parent families (Bos et al, 2016;Farr, 2017;Patterson, 2017;Calzo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis of 10 studies examining effects on children revealed that children of gay fathers had better outcomes than children of heterosexual parents, although the authors noted that the differences may have been attributed to gay fathers having higher socioeconomic status (Miller, Kors, & Macfie, ). Studies that have been published since this meta‐analysis have similarly found that gay fathers display attachment patterns with children that are comparable to or more secure than patterns of attachment between heterosexual fathers and children (McConnachie et al, ; for a review, see also Parke, ).…”
Section: Significant Developmentsmentioning
confidence: 89%
“…In terms of parent-child relationship quality, gay fathers showed greater responsiveness to their child than heterosexual parents in an observational assessment of parent-child interaction (Golombok et al 2014). When the same children were in early adolescence, those with gay fathers showed higher levels of secure-autonomous attachment and lower levels of disorganized attachment than children in heterosexual parent families (McConnachie et al 2020b). Although no differences were found between groups in child adjustment, rates of problems were high, resulting from these children's experiences of maltreatment prior to adoption (McConnachie et al 2020a).…”
Section: Gay Fathersmentioning
confidence: 95%